Effect of tannins from tropical plants on methane production from ruminants: A systematic review - E. Cardoso-Gutierrez (Elsevier, 2021)
Methane (CH4) is a greenhouse gas generated during the feed fermentation processes in the rumen. However, numerous studies have been conducted to determine the capacity of plant secondary metabolites to enhance ruminal fermentation and decrease CH4 production, especially those plants rich in tannins. This review conducted a descriptive analysis and meta-analysis of the use of tannin-rich plants in tropical regions to mitigate CH4 production from livestock. The aim of this study was to analyse the effect of tannins supplementation in tropical plants on CH4 production in ruminants using a meta-analytic approach and the effect on microbial population. Sources of heterogeneity were explored using a meta-regression analysis. Final database was integrated by a total of 14 trials. The ‘meta’ package in R statistical software was used to conduct the meta-analyses. The covariates defined a priori in the current meta-regression were inclusion level, species (sheep, beef cattle, dairy cattle, and cross-bred heifers) and plant. Results showed that supplementation with tropical plants with tannin contents have the greatest effects on CH4 mitigation . A negative relationship was observed between the level of inclusion and CH4 emission (−0.09), which means that the effect of CH4 mitigation is increasing as the level of tannin inclusion is higher. Therefore, less CH4 production will be obtained when supplementing tropical plants in the diet with a high dose of tannins.